Purple rice extract supplemented diet reduces DMH-induced aberrant crypt foci in the rat colon by inhibition of bacterial β-glucuronidase - Ratasark Summart (2018)
Background: Purple rice has become a natural product of interest which is widely used for health promotion. This study investigated the preventive effect of purple rice extract (PRE) mixed diet on DMH initiation of colon carcinogenesis. Materials and Methods: Rats were fed with PRE mixed diet one week before injection of DMH (40 mg/kg of body weight once a week for 2 weeks). They were killed 12 hrs after a second DMH injection to measure the level of O 6 -methylguanine and xenobiotic metabolizing enzyme activities. Results: In rats that received PRE, guanine methylation was reduced in the colonic mucosa, but not in the liver, whereas PRE did not affect xenobiotic conjugation, with reference to glutathione-S-transferase or UDP-glucuronyl transferase. After 5 weeks, rats that received PRE with DMH injection had fewer ACF in the colon than those treated with DMH alone. Interestingly, a PRE mixed diet inhibited the activity of bacterial β-glucuronidase in rat feces, a critical enzyme for free methylazoxymethanol (MAM) release in the rat colon. These results indicated that purple rice extract inhibited β-glucuronidase activity in the colonic lumen, causing a reduction of MAM-induced colonic mucosa DNA methylation, leaded to decelerated formation of aberrant crypt foci in the rat colon. Conclusions: The supplemented purple rice extract might thus prevent colon carcinogenesis by the alteration of the colonic environment, and thus could be further developed for neutraceutical products for colon cancer prevention.